A Critical Discourse Analysis of Indonesian Government’s Macroeconomic Policies toward Economic Development Aspects in National Budget Plan and Financial Memorandum (2012) Speech - Rendriawan Muhammad (Universitas Pendidikan Indonesia (UPI), 2015)
This Paper entitled “A Critical Discourse Analysis of Indonesian Government’s Macroeconomics Policies toward Economic Development Aspects in National Budget Plan and Financial Memorandum (2012) Speech”. It is aimed to investigate whether the Indonesian government’s economic development policies adhere to the 1945 Constitution. The study is qualitative in nature which utilizes van Dijk and Kintsch’s (1983) Semantic Representation Model. The data are the economic development policies which are elaborated in the National Budget Plan and Financial Memorandum presented before the Plenary Session of the House of Representatives by the Indonesian president Susilo Bambang Yudhoyono on August 16, 2011. The study revealed that the substance of each government’s policies and measures on economic development in the text are in accordance with the notion of the 1945 Constitution Chapter XIV Article 33 as a basic regulation of the national economy and social welfare. Moreover, those findings clarify that the government orients each economic development policies and measures toward the idea of the fifth point of Pancasila as the fundamental principle of democratic economy.Keywords: Macroeconomics, Economic Development, Critical Discourse Analysis, Democratic Economy, Semantic Representation Model